ICT-Based Learning Media in the Form of Powerpoint for Grade IV Elementary School Students - Marfiana, Reza; Ramadan, Zaka Hadikusuma (Universitas Pendidikan Ganesha, 2021)
The learning process was still not carried out effectively due to the lack of learning facilities. In addition, teachers only use lecture methods in providing materials. This causes students to get tired of learning. This research aimed to develop ICT-based learning media for grade IV elementary school students. This type of research was research development using ADDIE procedure. Product trial subjects numbered six experts. The methods used in collecting data were interviews, documentation and questionnaires. The instrument used in this study was a questionnaire with a Likert scale. The data analysis techniques in this study were qualitative descriptive analysis and quantitative descriptive analysis methods. The results of the study, namely learning media 3 in validation phase 1, obtained an average score of 83% and in the validation of stage 2 obtained results of 89%. This can be said in the learning media for learning three increased by 6%. Furthermore, in learning media 3 for the validation phase, 1 obtained an average score of 84% and in validation stage 2 got 92%. This can be said in the learning media for learning 4 increased by 8%. Then, for learning media 5 in validation phase 1, an average score of 83% and in the validation phase 2 obtained 92%. This can be said that the learning media for learning 5 had also increased by 9%. This shows ICT-based learning media in the form of powerpoints worthy of being applied to the learning process. This research implied that teachers could use the media developed by PowerPoint to help students with learning difficulties.